Thermal expansion coefficient of Diamond/SiC composites prepared by silicon vapor infiltration in vacuum. (January 2019) - Zheng, Wei; He, Xinbo; Wu, Mao; Ren, Shubin; Cao, Shunli; Guan, Dandan; Liu, Rongjun; Qu, Xuanhui
Abstract: Diamond/SiC composites were fabricated by Si-vapor reactive infiltration where graphite was used to generate SiC via an SiC reaction. The composites exhibited an inward growth of SiC and cracks within the diamond. In the strong interfacial bonding, Si diffusion occurred on the surface of the diamond. The thermal expansion coefficient (CTE) and thermal residual stress at different infiltration temperatures were simultaneously investigated. It was found that the CTE values increased from 1.2 to 4.5 × 10 −6 K −1 in the measured temperature range, while the presence of large-sized crushed diamond, high SiC content and high infiltration temperature enhanced the CTE values. In the low-temperature range, the measured CTEs agreed with those predicted by the Turner model; while in the high-temperature range they agreed with those predicted by the lower-bound Schapery model. Additionally, based on the Raman spectra, the thermal residual stresses were found to be 0.85, 1.76, 2.15 and 2.67 GPa at the infiltration temperatures of 1550, 1600, 1650, and 1700 °C, respectively. Highlights: High infiltration temperature would decrease the Si, improve the formation of SiC and lead to the crack of the diamond. CTE was increased by adopting the large crushed diamond, more SiC and higher infiltration temperature. CTE was predicted by the method of the second iteration based on assumption of the core-shell model. Thermal residual stresses were respectively 0.85, 1.76, 2.15 and 2.67 GPa from 1550, 1600, 1650 to 1700 °C.